Conical surrounding gate MOSFET: a possibility in gate-all-around family. (15th February 2016) - Jena, B; Ramkrishna, B S; Dash, S; Mishra, G P
Abstract: In this paper a new conical surrounding gate metal-oxide-semiconductor field effect transistor (MOSFET) with triple-material gate has been proposed and verified using TCAD device simulator from Synopsis. The electrostatic performance of conical model with different tapering ratios is extensively investigated and compared with that of cylindrical model (tapering ratio TR = 1). The present model exhibits improved electrostatic behavior for an optimized tapering ratio of 0.98 as compared to the conventional cylindrical model. The results reveal that the triple-material conical model provides better ON current performance, transconductance and reduced threshold voltage. On the contrary the single-material conical model exhibits maximum / ratio, minimum OFF current and reduced subthreshold swing (SS) in comparison to other models. Thus, the conical model with optimized tapering ratio can be a possible replacement of cylindrical model for low-power and high speed application.